Qualification of gamma spectrometry measurement for the radiological characterization of mixed VLLW cables in particle accelerators. (December 2020) - Rimlinger, Maeva; Frosio, Thomas; Menaa, Nabil; Magistris, Matteo; Theis, Chris
Abstract: In the framework of maintenance activities in particle accelerators, such as upgrades and dismantling, a large number of activated equipment are removed from the accelerator complex and require characterization in view of their disposal as radioactive waste. In particular, cables can be of different types. This feature induces variations of the efficiency calibration curves due to the variation of the material composition, source distribution and density. Hence, quantifying the activities of the gamma-emitting radionuclides can be quite challenging for mixed cables. In this article, we propose a new qualification methodology, based on gamma spectrometry, in order to assess the activity results uncertainties of gamma-emitting radionuclides. This new methodology is developed to define the envelop efficiency calibration curves and allows for the establishment of more accurate activity values with their corresponding uncertainties. Highlights: New gamma spectrometry qualification method to characterize mixed material equipment for elimination as very-low-level radioactive waste Quantification of gamma spectrometry uncertainties due to geometry variations of waste activated in particle accelerators Generation of efficiency calibration curves taking into account geometry parameter variations